2017
DOI: 10.5217/ir.2017.15.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Japanese physicians' attitudes towards enteral nutrition treatment for pediatric patients with Crohn's disease: a questionnaire survey

Abstract: Background/AimsEnteral nutrition (EN) is recommended for the treatment of pediatric Crohn's disease (CD) in Japan. However, the indications and treatment protocols for EN vary among hospitals. In the present study, we aimed to determine how EN was administered to pediatric patients and whether physicians followed treatment guidelines in their practices.MethodsTwo types of questionnaires were administered to 32 physicians who were involved in the treatment of pediatric CD. The consensus questionnaire evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
0
13
2
Order By: Relevance
“…The current study found that all respondents would definitely or probably use EEN to induce remission in newly diagnosed CD compared to a previous survey, which found that only 60% of respondents felt EEN to be appropriate for CD . The reported rates of usage of EEN for active CD are greater than that reported by European and Japanese physicians . In the current study, EEN was more commonly used for CD with moderate to severe disease activity than for children with mild disease activity.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…The current study found that all respondents would definitely or probably use EEN to induce remission in newly diagnosed CD compared to a previous survey, which found that only 60% of respondents felt EEN to be appropriate for CD . The reported rates of usage of EEN for active CD are greater than that reported by European and Japanese physicians . In the current study, EEN was more commonly used for CD with moderate to severe disease activity than for children with mild disease activity.…”
Section: Discussioncontrasting
confidence: 63%
“…However, other international practices differ widely; previous surveys indicated that 52% of Swedish clinicians recommend 6 weeks’ duration, whilst 30% of North American clinicians recommend less than 6 weeks and 46% recommend 6–8 weeks’ duration . In contrast, in a different assessment, Japanese gastroenterologists only prescribed EEN for a mean duration of 15.9 days in children with active CD …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a previous study by Souza et al revealed that the consumption of amino acid diets can exacerbate experimental colitis [24], clinical outcomes suggest the opposite. Exclusive enteral nutrition with ED amino acids has been used extensively for the application of IBD therapy, and this has been proven effective in achieving and maintaining remission [25,26]. During an inflammatory flare, IBD patients are at a high risk of nutrient depletion, and this is particularly true for children [27].…”
Section: Discussionmentioning
confidence: 99%